Sistem Informasi Profil Kelompok Pertanian Terpadu Berbasis Web dengan Integrated Farming (Studi Kasus: Desa Dawuhan, Malang) - Soebroto, Arief Andy; Hidayat, Nurul; Perdana, Rizal Setya; Indriati, Indriati; Darmawan, Hendra; Brilliansyach, Raihan Fikri; Ibnu, Mohammad; Nurannisa, Nadhira; Vasya, M Azka Obila (LPPM STIKI MALANG, 2024)
Dawuhan Village in Poncokusumo District, Malang Regency, is an evolving village with significant potential in the livestock sector. However, livestock data management in this village is still done manually, facing various challenges such as limited access, data integrity issues, and time-consuming processes. To address these issues, this research aims to develop a Web-Based Integrated Livestock Group Profile Information System. The primary objectives of this study are to improve accessibility, streamline the livestock data management process, and enhance data accuracy and security. The system is designed using the Next.js framework, chosen for its ease of use and security in implementing authentication and authorization, as well as its capability for future integration. The research results show that the developed system functions according to the requirements, providing a more efficient platform, reducing errors, and enhancing the user experience for farmers involved in data management. The implementation of this system is expected to improve operational efficiency and livestock data management in Dawuhan Village comprehensively.